Modular Number Theory

Number Theory Level pending

For all positive integer n n , is it always true that 3 2 n + 2 8 n 9 0 ( m o d 64 ) 3^{2n+2}-8n-9 \equiv 0 \pmod{64} ?

Yes No

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Max Patrick
Oct 3, 2019

Let the equation be true for n equal to some non-negative integer a. Note that it is true for n=0.

3 2 a + 2 8 a 9 0 ( m o d 64 ) 3^{2a+2}-8a-9\equiv 0 \pmod{64}

multiply through by 9

3 2 a + 4 72 a 81 0 ( m o d 64 ) 3^{2a+4}-72a-81\equiv 0 \pmod{64}

3 2 a + 4 8 a 8 9 64 a + 64 ( m o d 64 ) 3^{2a+4}-8a-8-9\equiv 64a+64 \pmod{64} (multiples of 64 are of course 0 (mod 64))

3 2 a + 4 8 a 8 9 0 ( m o d 64 ) 3^{2a+4}-8a-8-9\equiv 0 \pmod{64}

3 2 ( a + 1 ) + 2 8 ( a + 1 ) 9 0 ( m o d 64 ) 3^{2(a+1)+2}-8(a+1)-9\equiv 0 \pmod{64}

Thus if the equation is true for any n=a it is also true for n=a+1. It is true for n=0. Proof by induction.

Chew-Seong Cheong
Sep 28, 2019

Similar solution with @David Vreken 's

N = 3 2 n + 2 8 n 9 = 9 n + 1 8 n 8 1 = ( 8 + 1 ) n + 1 8 ( n + 1 ) 1 = k = 0 n + 1 ( n + 1 k ) 8 k 8 ( n + 1 ) 1 = k = 2 n + 1 ( n + 1 k ) 8 k + 8 ( n + 1 ) + 1 8 ( n + 1 ) 1 = k = 2 n + 1 ( n + 1 k ) 8 k = 64 k = 0 n + 1 ( n + 1 k + 2 ) 8 k 0 (mod 64) \begin{aligned} N & = 3^{2n+2} - 8n - 9 \\ & = 9^{n+1} - 8n - 8 - 1 \\ & = {\color{#3D99F6}(8+1)^{n+1}} - 8(n+1) - 1 \\ & = {\color{#3D99F6}\sum_{k=0}^{n+1}\binom {n+1}k 8^k} - 8(n+1) - 1 \\ & = {\color{#3D99F6}\sum_{\color{#D61F06}k=2}^{n+1}\binom {n+1}k 8^k + 8(n+1)+1} - 8(n+1) - 1 \\ & = \sum_{\color{#D61F06}k=2}^{n+1}\binom {n+1}k 8^k \\ & = 64\sum_{\color{#3D99F6}k=0}^{n+1}\binom {n+1}{\color{#3D99F6}k+2} 8^k \\ & \equiv \boxed{\text{0 (mod 64)}} \end{aligned}

Yes , it is always true.

David Vreken
Sep 28, 2019

3 2 n + 2 8 n 9 3^{2n + 2} - 8n - 9

= 3 2 ( n + 1 ) 8 n 9 = 3^{2(n + 1)} - 8n - 9

= 9 n + 1 8 n 9 = 9^{n + 1} - 8n - 9

= ( 8 + 1 ) n + 1 8 n 8 1 = (8 + 1)^{n + 1} - 8n - 8 - 1

= ( 8 + 1 ) n + 1 8 ( n + 1 ) 1 = (8 + 1)^{n + 1} - 8(n + 1) - 1

= ( ( n + 1 n + 1 ) 8 n + 1 1 0 + ( n + 1 n ) 8 n 1 1 + ( n + 1 n 1 ) 8 n 1 1 2 + . . . + ( n + 1 2 ) 8 2 1 n 1 + ( n + 1 1 ) 8 1 1 n + ( n + 1 0 ) 8 0 1 n + 1 ) 8 ( n + 1 ) 1 = ({{n + 1} \choose {n + 1}}8^{n + 1}1^{0} + {{n + 1} \choose {n}}8^{n}1^{1} + {{n + 1} \choose {n - 1}}8^{n - 1}1^{2} + ... + {{n + 1} \choose {2}}8^{2}1^{n - 1} + {{n + 1} \choose {1}}8^{1}1^{n} + {{n + 1} \choose {0}}8^{0}1^{n + 1}) - 8(n + 1) - 1 (by the binomial expansion)

= ( k 8 2 + ( n + 1 ) 8 + 1 ) 8 ( n + 1 ) 1 = (k8^2 + (n + 1)8 + 1) - 8(n + 1) - 1 (for some integer k k )

= k 8 2 = k8^2

= 64 k = 64k

Since 64 k 64k is always divisible by 64 64 , 3 2 n + 2 8 n 9 0 ( m o d 64 ) 3^{2n + 2} - 8n - 9 \equiv 0 \pmod{64} is always true .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...